Financing food systems transformation: Using the Special Drawing Rights more strategically - Díaz-Bonilla, Eugenio (2021)
Eugenio Diaz Bonilla SPECIAL EVENT Funding Food System Transformation in Developing Countries: An example from Ethiopia UNFSS Side Event -- Co-organized by IFPRI, The Alliance of Bioversity International and CIAT, CGIAR SEP 24, 2021 - 08:00 AM TO 09:30 AM EDT